Dynamic compressive mechanical properties of the spiral tungsten wire reinforced Zr-based bulk metallic glass composites. (15th October 2020) - Chen, S.; Li, W.Q.; Zhang, L.; Fu, H.M.; Li, Z.K.; Zhu, Z.W.; Li, H.; Zhang, H.W.; Wang, A.M.; Wang, Y.D.; Zhang, H.F.
Abstract: In this study, bulk metallic glass composite (BMGC) reinforced with a novel spiral structure of tungsten wires was prepared. The composite exhibits a high ultimate strength of 2830 MPa and a large plasticity of 26% under quasi-static compression. The dynamic compressive mechanical properties of this BMGC were also systematically investigated by split Hopkinson pressure bar technique. It is found that the yield stress of the composite under uniaxial compression increases firstly and then decreases with increasing the strain rate. To describe the strain-rate dependence of the yielding behavior of the composite, a constitutive model considering adiabatic shear localization was established. Furthermore, the deformation and fracture behaviors of the composite under quasi-static and dynamic compression were discussed in detail. Different from the tungsten fiber reinforced bulk metallic glass composites (BMGCs), the spiral tungsten wire reinforced BMGC fractured in a shear mode, which is distinctly favorable to the self-sharpening capability. These findings could deepen the understanding of deformation behaviors and failure modes of BMGCs and promote their applications.